Micropyrones A and B, two new α-pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch. Issue 3 (1st February 2023) - Xu, Ying-Ting; Luo, Yu-Cai; Xue, Jing-Hua; Li, Yu-Ping; Dong, Lei; Li, Wen-Jun; Zhou, Zhong-Yu; Wei, Xiao-Yi
Abstract: Two new α -pyrones, micropyrones A (1 ) and B (2 ), along with four known γ -pyrones, nocapyrone D (3 ), nocapyrone A (4 ), marinactinone A (5 ), and nocapyrone H (6 ), were isolated from the culture extract of actinomycete Microbacterium sp. GJ312, which was isolated from Glycyrrhiza uralensis . The structures of these compounds were identified by analysis of spectral data. They are the first α - and γ -pyrones reported from the genus Microbacterium . The antibacterial activity of all compounds against Staphylococcus aureus and methicillin resistant S. aureus was evaluated. However, none of them showed significant activity. This study represents the first phytochemical example of a Glycyrrhiza -derived actinomycete. Graphical Abstract: UF0001